Changes in Quality of Care after Hospital Mergers and Acquisitions - Beaulieu, Nancy D; Dafny, Leemore S; Landon, Bruce E; Dalton, Jesse B; Kuye, Ifedayo; McWilliams, J. Michael (The New England journal of medicine, 2020)
Measures of health care quality were compared between 246 hospitals that were acquired by another hospital or health system during 2009–2013 and 1986 control hospitals that were not acquired. A composite measure of patient-reported experience worsened slightly in acquired hospitals relative to control hospitals. There were no significant changes in mortality or readmission rates.